The The Rise of Start Up of Young Entrepreneurs in Time of COVID-19 Pandemic in the Economic Growth Center of Legazpi City - Llamasares, Sheila Mae (JPAIR Multidisciplinary Research, 2023)
Microbusinesses are booming nationwide, including in Legazpi. Small enterprises closed, personnel resigned at historical rates, and the global supply chains were disrupted during the pandemic. Disaster-prone areas struggled with COVID-19's economic and regulatory limitations. The government's aid isn't enough to support a family, notably in lockdown areas. Some young people began businesses to survive this epidemic situation. This qualitative research investigated how to create an intervention program to help start-up young entrepreneurs overcome the COVID-19 pandemic crisis. If Legazpi City's five growth centers—Bigaa, Bitano, Capantawan, Washington, and Taysan—could surmount their young entrepreneurs' challenges, economic activity would rise, as would businesses. The results proved that making a profit drives the respondents. According to the findings, most young entrepreneurs have difficulty accessing capital. This study is vital to humanity's survival in the current crisis. Thus, the proposed intervention program must focus on either exploring or implementing innovative forms of marketing or a more refined version of an already successful business strategy to solve the young entrepreneurs' struggles with access to capital that would be alleviated if these laws were universally applied.
Keywords: Entrepreneurship; proposed intervention program; profit; challenges; young entrepreneur; micro-scale business; qualitative; Philippines